The Social Organization of Quality of Life of Older People in Long-Term Care Facilities: An Institutional Ethnography Approach - Naomi Hlongwane; Lieketseng Ned (Global Qualitative Nursing Research)
With the growing population in South Africa, there is a need for long-term care facilities. Using institutional ethnography, this study investigates the quality of life for older adults in South African long-term care facilities. Twenty key informants and 10 staff members were purposively sampled across 5 long-term care facilities in Gauteng, South Africa, for participation in in-depth interviews and observations. An analysis of institutional texts was conducted, focusing on legislative frameworks and practices. The findings include three analytic threads, namely: (a) Healthcare Access and Physical Well-Being, (b) Institutional Constraints on Meaningful Engagement, and (c) Efficiency Overriding Privacy and Autonomy. A significant gap exists between legislative policies and actual practices, with older adults seeking more autonomy and decision-making involvement. This institutional ethnography, rooted in the perspectives of older residents and care workers, highlights how long-term care facilities are shaped by regulatory frameworks and institutional ideologies. These frameworks often restrict care workers in fully leveraging their intimate knowledge of residents to address individual needs, as their care work interventions are bound to compliance with the textual and accountability demands of the Older Persons Act 13 of 2006.